Introduction to food engineering - Singh, R. Paul (Elsevier/Academic Press, 2009)
This edition of 'Introduction to Food Engineering' presents the engineering concepts and unit operations used in food processing, in a unique and challenging blend of principles with applications.
Keywords: Food industry and trade.; elektronické knihy; electronic books